2016
DOI: 10.1590/s1678-9946201658070
|View full text |Cite
|
Sign up to set email alerts
|

SEROPREVALENCE AND RISK FACTORS ASSOCIATED WITH Toxoplasma gondii INFECTION AMONG RURAL COMMUNITIES IN NORTHERN IRAN

Abstract: SUMMARYToxoplasmosis is the fourth most common cause of hospitalization and the second cause of death due to food-borne infections. We conducted a cross-sectional study to determine the prevalence, disease awareness and risk factors associated with toxoplasmosis among rural communities in Northern Iran. Data were obtained from serological testing and from participant's questionnaires and were analyzed using a logistic regression. Of the 630 participants, 465 (73.8%), and 12 (1.9%) had IgG and both IgG and IgM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 31 publications
(53 reference statements)
7
31
1
Order By: Relevance
“…Furthermore, more rural population and also agricultural and husbandry activities of people living in Mazandaran province could be another explanation for high prevalence of parasitic infection in this area. 34,35 Also our results showed most prevalent helminthes infection was Trichostrongylus spp., and it is in agreement with recent studies in north of Iran. 36,37 Globally, earlier investigations demonstrated several risk factors for the high prevalence and incidence of IPIs including poor sanitation, low family income, poor personal hygiene, untreated water supply, low level of self and parental education, eating unwashed vegetables, contact with animals and contaminated soils.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, more rural population and also agricultural and husbandry activities of people living in Mazandaran province could be another explanation for high prevalence of parasitic infection in this area. 34,35 Also our results showed most prevalent helminthes infection was Trichostrongylus spp., and it is in agreement with recent studies in north of Iran. 36,37 Globally, earlier investigations demonstrated several risk factors for the high prevalence and incidence of IPIs including poor sanitation, low family income, poor personal hygiene, untreated water supply, low level of self and parental education, eating unwashed vegetables, contact with animals and contaminated soils.…”
Section: Discussionsupporting
confidence: 57%
“…In this finding is consistent with some of the studies from Iran and other countries which showed consumption of undercooked meat is an important factor for parasite transmission. 8,26 Method of cooking meat in the form of Kebab (undercooked meat) is quite common in the area that the current study was performed.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] The appropriate geographic conditions for the development of T. gondii oocysts, the food and health habits of a community, and the exposure to toxoplasmosis-related risk factors play an important role in the prevalence of toxoplasmosis in a community. 7,8 The global seropositivity of T. gondii infection in cancer patients and control was reported 26% and 12.1%. 9 Prevalence of toxoplasmosis in Iran was reported 39.3% in the general population, 51.01% in immunocompromised patients and 43% in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…The infection is usually asymptomatic or produces only mild symptoms. Severe complications can occur in certain groups: encephalitis, brain abscesses and death in immunocompromised individuals [13,14], pre-eclampsia, psychiatric disorders, abortion and foetal abnormality in pregnant women [15,16,17], and behavioural changes, neuropsychiatric disorders, and infertility in healthy humans and animals [18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%